A Mobile App For Community Association - Goh, Chong Xian (2020)
Existing residential community association management is a hassle and manual process as it involves many handiworks that require a large number of time and cost. These behind time operations had caused decreasing in efficiency and effectiveness, which results in bad influences on the residence’ image. Therefore, this project aims to investigate and analyse the root causes of the predicament and provide a solution to it. The main causes discovered including heavily rely on paperwork, outdated operational workflow, poor privacy concerns on personal information of residents, etc. A system that involving Ruby on Rails API backend server, Vue.js web admin panel, Flutter mobile application for residents was proposed to tackle the aforementioned problems. Furthermore, Kanban Agile methodology was practiced throughout the implementation phase to manage work tasks and visualize the project progress. The proposed system reduced the manual work of fee payment, increase the announcement delivers effectiveness by instant notification of the mobile application. In addition, the mobile application provides an official channel for residents to submit their feedback and visitor application and track the progress.